Microbial analysis of raw and pasteurized milk from selected areas of Dinajpur, Bangladesh (Asian Journal of Medical and Biological Research, 2015)
Milk is highly vulnerable to microbial contamination and consequently is easily perishable. The aim of the present study was microbial analysis of raw and pasteurized milk. For this, a total of 32 milk samples (12 from raw milk and 20 from pasteurized milk) were collected from 8 sources. Among them three were raw (R1 to R3) sources and rest five were pasteurized milk (P1 to P5) sources. Each of the collected samples was investigated during the period from May to December, 2012. All milk samples were subjected to total viable count (TVC), total coliform count (TCC), Total Staphylococcus count (TSC) and Grams staining to determine the loads of microbes in raw and pasteurized milk. Total viable counts (TVC) range of 12 raw milk samples (R, R2 and R3) were 1.3 x106 to 7.4 x105 cfu/ml. The presence of Escherichia coli in the raw milk samples were from 2.3 x102 to 9.4 x102 cfu/ml, but the presence of Staphylococcus were from 5.9 x102 to 7.9 x102 cfu/ml. Whereas, the range of TVC for five brands of pasteurized milk (P1, P2, P3, P4, and P5) were from 1.8 x104 to 9.8 x104 cfu/ml, TSC were from 2.8 x10 to 8.6 x102 cfu/ml and TCC from 1.01 x102 to 9.1 x10 cfu/ml. Therefore, it can be concluded that high counts of bacteria were found in raw milk and pasteurized milk. The government therefore should conduct frequent inspection of the marketed milks to check whether they meet the minimum legal standards and should monitor the overall hygienic condition surrounding the production and handling of milk. Realistic standards for the raw milks need to be devised and appropriate training should be given to the raw milk producers in hygienic handling of milk.Asian J. Med. Biol. Res. June 2015, 1(2): 292-296